Fabrication of phytic acid embellished kaolinite and its effect on the flame retardancy and thermal stability of ethylene vinyl acetate composites. Issue 46 (19th July 2021) - Zhang, Huimin; Meng, Dan; Wang, Wenjia; Li, Hongfei; Gu, Xiaoyu; Zhang, Sheng; Sun, Jun; Xin, Fei; Qin, Zuodong; Tang, Wufei
Abstract: A modified kaolinite by grafting with phytic acid (PA‐g‐Kaol) is fabricated, and it was introduced into ethylene vinyl acetate (EVA) with intumescent flame retardancy (IFR) together to improve the flame retardancy of EVA composites. The results show the limiting oxygen index value of EVA/ (18.0 wt% IFR)/ (2.0 wt% PA‐g‐Kaol) is 30.8%. Meanwhile, there is only one dripping produced in the vertical burning test. What's more, the flame‐retardant mechanism is demonstrated by TG‐IR, real‐time‐IR and GC–MS analysis. The results indicate that some pyrolytic products of IFR and PA‐g‐Kaol, like ammonia and phosphoric acid, catalyze the crosslinking of EVA and flame retardant, the resultant compact char protects the substrate from further burning. Abstract : Through grafting with PA and APTES on the surface of Kaol to obtain PA‐g‐Kaol, then melt blend with EVA material and intumescent flame retardant to prepare the flame retardant polymer composites. As well as the flame retardant mechanism was explored.